A Framework for Developing and Implementing An Online Learning Community - Elaine Khoo; Bronwyn Cowie (Flexible Learning Association of New Zealand, 2020)
Developing online learning communities is a promising pedagogical approach in online learning contexts for adult tertiary learners, but it is no easy task. Understanding how learning communities are formed and evaluating their efficacy in supporting learning involves a complex set of issues that have a bearing on the design and facilitation of successful online learning experiences. This paper describes the development of a framework for understanding and developing an online learning community for adult tertiary learners in a New Zealand tertiary institution. In accord with sociocultural views of learning and practices, the framework depicts learning as a mediated, situated, distributed, goal-directed, and participatory activity within a socially and culturally determined learning community. Evidence for the value of the framework is grounded in the findings of a case study of a semester-long fully online asynchronous graduate course. The framework informs our understanding of appropriate conditions for the development and conduct of online learning communities. Implications are presented for the design and facilitation of learning in such contexts.